Does work-family conflict explain the direct and indirect role effects of perceived organizational support and job satisfaction? Evidence in the Indonesian banking - Muzakki Muzakki; Asep Heryyanto (Proceeding of The International Conference on Economics and Business, 2022)
The purpose of this study is to investigate both the influences of perceived organizational support and work-family conflict on job satisfaction. In addition, this research aims to investigate the impact of the mediation of work-family disputes in the connection between perceived organizational support and job satisfaction. We utilize a quantitative approach to acquire data from the subject of the study. For the sampling strategy, we employ random sampling with questionnaire distribution as the data collection tool. The data analysis method was called Structural Equation Modeling Partial Least Square (SEM-PLS). In addition, the findings of this research indicate that a favorable and significant influence on work satisfaction may be attributed to a perceived high level of organizational support. The perception of organizational support is another factor that contributes negatively to work-family conflict. Meanwhile, the tension between work and family life has a positive and noticeable impact on job satisfaction. The latest finding is that work and family conflict might be a negative mediator in the association between perceived organizational support and job satisfaction.